(untitled) (Iter, 2022)
The lesson is structured around the human truth that expressed in words and implies an active relationship between subjects communicating among themselves, and also with that are shown and, somehow, request to be known. A ristotel ian-Thom is tic theory States that, in order to have true knowledge, the relationship o f the knower with what is known musí result in a conversión, adaptation or assimilation, o f one into the other. Despite its being in high disrepute today, this is still the mandatory starting point fo r every reflection on the subject. Human truth is always relative and not absolute, and it is sometimes joined to lies or errors. The compass settling the truth-lie divergence and suggesting the convenience o f choosing one or the other is righteousness. Acting well and conscientiously, guarantees that we are true.